Achilles' new heel: Shock absorbing, gait assisting and energy harvesting. (May 2023) - Pan, Qiqi; Long, Zhihe; Zhang, Zhuomin; Lin, Weikang; Zhang, Lingling; Bai, Songnan; Yang, Xiaodan; Liu, Shiyuan; Park, Yong-Lae; Chirarattananon, Pakpong; Yang, Zhengbao
Abstract: Humans have evolved to walk highly efficiently to conserve energy, making it challenging to develop assistive and energy-harvesting devices for walking. Herein, we report a heel pad-based assistance device for walking that not only optimizes the energetic economy of walking and prevents plantar fasciitis but also harvests energy from heel impact. Our footwear-embedded device improves the walking economy by offering shock absorption and walking assistance, while simultaneously providing energy-harvesting functions. We demonstrate that the use of our device reduces the activation of the gastrocnemius and soleus muscles during the foot strike by 5.8 ± 1.0 % and 4.1 ± 0.6 %, respectively. The collisional energy conserved from the impact at the touchdown is transformed into 3.8 ± 0.3 watts of electrical power (mean ± SEM). Compared with walking in normal shoes, the energy savings with the device imply that walking endurance could be increased by as much as 10 % without extra effort from the wearer. Our findings demonstrate the potential of the heel pad-based device that enhances the energy economy of walking and human bipedal locomotion. Graphical Abstract: ga1 Highlights: Highly integrated footwear for shock absorbing, gait assisting, and energy harvesting. A power density of 27.5 mW/cm 3 (peak power: 3.8 Watts) is achieved for a single step. Walking with the device does not significantly interfere with the normal gait pattern. The footwear device shows stable durability and robustness in daily locomotion.